Green and Resilient Automotive Supply Chains: Bibliometric and Systematic Review Toward Sustainable Manufacturing Competitiveness - Andri Mulyana; Deri Maryadi; Abdul Rochim (PROGRAM STUDI TEKNIK INDUSTRI UNIVERSITAS TRIDINANTI, 2026)
The automotive manufacturing industry is experiencing significant transformation driven by increasing global competition, supply chain complexity, and the rapid development of Industry 4.0 technologies. Traditional lean-oriented supply chains, which primarily focus on operational efficiency and waste reduction, are increasingly challenged by global disruptions, sustainability pressures, and the need for resilience. This study aims to analyze the development of research trends related to automotive supply chain transformation during the period 2015–2025, identify dominant research themes, and explore the role of Industry 4.0 technologies in supporting supply chain transformation within the automotive manufacturing sector. This study employs a Systematic Literature Review (SLR) combined with bibliometric analysis using data collected from the Scopus database. The analysis focuses on publications related to supply chain management and automotive manufacturing published between 2015 and 2025. The study examines publication trends, journal sources, leading authors, territorial distribution, and thematic evolution associated with Lean Supply Chain, resilience, sustainability, and Industry 4.0 technologies. The findings indicate a significant increase in research publications, particularly after the COVID-19 pandemic, reflecting a paradigm shift from efficiency-oriented supply chains toward resilient automotive ecosystems. The dominant research themes include Lean Supply Chain, digital transformation, supply chain resilience, and sustainability. Technologies such as Internet of Things (IoT), big data analytics, blockchain, and artificial intelligence play important roles in improving supply chain visibility, flexibility, and responsiveness. The study concludes that the integration of Lean Supply Chain, Industry 4.0, resilience, and sustainability has become a strategic direction for future automotive supply chain development. This research contributes to the literature by providing a comprehensive overview of the evolution of automotive supply chain transformation and highlighting future research opportunities in resilient and digital automotive ecosystems..